Wellness Beyond Words : Maya Compositions of Speech and Silence in Medical Care - Harvey, T. S., 1972- (Book collections on Project MUSE., 2013)
This anthropological account of Maya language use in health care in highland Guatemala explores some of the cultural and linguistic factors that can complicate communication in the practice of medicine. Bringing together the analytical tools of linguistic and medical anthropology, the author offers a rare comparative glimpse into Maya intra-cultural therapeutic and cross-cultural biomedical interactions. --